Peer Review and Medical Journals - Kenneth Nugent; Christopher J. Peterson (SAGE Publishing, 2024)
Journal editors depend on peer reviewers to make decisions about submitted manuscripts. These reviewers help evaluate the methods, the results, the discussion of the results, and the overall organization and presentation of the manuscript. In addition, reviewers can help identify important mistakes and possible misconduct. Editors frequently have difficulty obtaining enough peer reviews which are submitted in a timely manner. This increases the workload of editors and journal managers and potentially delays the publication of clinical and research studies. This commentary discusses of the importance of peer reviews and make suggestions which potentially can increase the participation of academic faculty and researchers in this important activity.